Strategi Membangun Brand Image Yang Kuat Dengan Fokus Pada Image Branding Di Pt Distribusi Sukses Mandiri - Suryasuciramadhan, Arfian; Irsyad, Alif Dava; Setiawan, Najib; Haris, Istialdi Pratama; Latief, Lika Mulki; Putri, Ninda Ela (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This research aims to build a strong brand image at the company PT DISTRIBUSI SUKSES MANDIRI, with a focus on image branding, the research method used is qualitative with literature study techniques. The results showed that PT DISTRIBUSI SUKSES MANDIRI implemented several key strategies, including brand communication, effective use of social media and strategic places. Clear and engaging communication, as well as responsive interaction on social media, contribute significantly to the company's positive image in the eyes of consumers. In addition, a focus on quality customer service helps create loyalty and trust. This research is to develop an effective branding strategy and maintain customer loyalty.